2015
DOI: 10.1380/ejssnt.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structures of a Well-Defined Organic Hetero-Interface: C<sub>60 </sub>on Pentacene Single Crystal

Abstract: Electronic structures of donor-acceptor hetero-interfaces are crucial for performance of organic solar cell devices. In the present study, a well-defined organic molecular interface of pentacene single crystal and C60 overlayer is elucidated by x-ray and ultraviolet photoelectron spectroscopy (XPS and UPS) and photoelectron yield spectroscopy (PYS). An energy level diagram at this hetero-molecular contact in the "head-on" orientation is derived, which reveals the vacuum level alignment and flat-band conditions. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…On account of the formation of electronic bands and the associated delocalization of charge carriers, [1][2][3] reasonably high charge carrier mobility has been reported in devices of single crystalline organic semiconductors. Figure 2 insets show typical AFM images of the Pn-SC samples covered with 20 nm-thick C 60 overlayers grown at various substrate temperatures, i.e., 160, 300, and 370 K. C 60 forms grains on the Pn-SC surface in the case of RT (300 K) growth as reported previously, [23,31] and it was found that the lateral sizes and shapes of these grains vary depending on the growth temperature. Proportional increase of the inplane mean crystallite size of C 60 with the growth temperature suggests importance of surface diffusion processes of the C 60 molecules on the Pn-SC surface as a leading factor for determination of the heterojunction structures.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…On account of the formation of electronic bands and the associated delocalization of charge carriers, [1][2][3] reasonably high charge carrier mobility has been reported in devices of single crystalline organic semiconductors. Figure 2 insets show typical AFM images of the Pn-SC samples covered with 20 nm-thick C 60 overlayers grown at various substrate temperatures, i.e., 160, 300, and 370 K. C 60 forms grains on the Pn-SC surface in the case of RT (300 K) growth as reported previously, [23,31] and it was found that the lateral sizes and shapes of these grains vary depending on the growth temperature. Proportional increase of the inplane mean crystallite size of C 60 with the growth temperature suggests importance of surface diffusion processes of the C 60 molecules on the Pn-SC surface as a leading factor for determination of the heterojunction structures.…”
Section: Introductionsupporting
confidence: 63%
“…[15][16][17] In the present work, the evolution of the crystallinity of a well-ordered bimolecular heterojunction, C 60 on a single crystal surface of pentacene (C 22 H 14 ), is studied depending on the growth temperature by means of surface X-ray diffraction techniques and noncontact mode atomic force microscopy (nc-AFM). [18] The pentacene/C 60 interface has been studied widely, both experimentally [19][20][21][22][23][24] and theoretically. [18] The pentacene/C 60 interface has been studied widely, both experimentally [19][20][21][22][23][24] and theoretically.…”
mentioning
confidence: 99%
“…Yamamoto and co-authors carried out the high-resolution XPS and UPS measurements on the epitaxial heterointerface of C 60 on the Pn-SC samples. 251 The experimental setup was same as that described in Section III.2.(2). For the sake of deducing the interface electronic structures, evolution of the photoelectron spectra in the core-levels, valence bands, and secondary electron cut-off regions was systematically tracked as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we consider the D/A bilayer heterojunction structure comprising pentacene as the electron donor and C 60 as the acceptor. The PEN/C 60 bilayer heterojunction is one of the most prototypical organic solar cells; 52,53 the electronic structures of the PEN/C 60 interfaces have been investigated in numerous studies, including ultraviolet photoelectron spectroscopy, [54][55][56] external quantum efficiency (EQE) measurements, 57,58 microelectrostatic calculations, 59 and ab initio methods. 8,9 According to the X-ray diffraction measurement, 57 the PEN/C 60 interface morphology is dominantly an edge-on orientation.…”
Section: B Application To Pen/c 60 Interfacementioning
confidence: 99%